Investor Protection and Corporate Governance: Evidence from Worldwide CEO Turnover - DEFOND, MARK L.; HUNG, MINGYI (Journal of Accounting Research, 2004)
ABSTRACT Recent research asserts that an essential feature of good corporate governance is strong investor protection, where investor protection is defined as the extent of the laws that protect investors' rights and the strength of the legal institutions that facilitate law enforcement . The purpose of this study is to test this assertion by investigating whether these measures of investor protection are associated with an important role of good corporate governance: identifying and terminating poorly performing CEOs. Our tests indicate that strong law enforcement institutions significantly improve the association between CEO turnover and poor performance, whereas extensive investor protection laws do not. In addition, we find that in countries with strong law enforcement, CEO turnover is more likely to be associated with poor stock returns when stock prices are more informative. Finding that strong law enforcement institutions are associated with improved CEO turnover‐performance sensitivity is consistent with good corporate governance requiring law enforcement institutions capable of protecting shareholders' property rights (i.e., protecting shareholders from expropriation by insiders). Finding that investor protection laws are not associated with improved CEO turnover‐performance sensitivity is open to several explanations. For example, investor protection laws may not be as important as strong law enforcement in fostering good governance, the set of laws we examine may not be the set that are most important in promoting good governance, or measurement error in our surrogate for extensive investor protection laws may reduce the power of our test of this variable.